Examining the measurement of severity of intimate partner violence and its association to mental health outcomes: a narrative synthesis - White, Sarah; Bearne, Lindsay; Sweeney, Angela; Mantovani, Nadia (Frontiers in Public Health, 2024)
The aims of this synthesis were to investigate the relationship between IPV severity and mental health outcomes and shed light to gaps and limitations in existing methodologies used to assess IPV severity and its association with mental health outcomes. We conducted a two-stage narrative synthesis of 76 studies. First, we identified IPV measures used in at least five studies, focusing on their variations and severity score calculation. Then, we analysed findings of studies correlating IPV severity with mental health outcomes, identifying features of measures and statistical methods influencing result consistency. Measures of intimate partner violence were often modified from their original, potentially impact on the reliability and validity of these measures. The operationalization of violence severity varied across studies, leading to inconsistencies in scoring whereby compromising the consistency of severity levels across studies. We found lack of consistency in applying validated methods for scoring instruments to determine abuse severity. In this review, we consistently found that the severity of IPV and its various subtypes were linked to different mental health outcomes across multiple studies. We discovered evidence suggesting that experiencing more types of IPV was associated with worse mental health outcomes. Generally, higher levels of overall IPV severity and its specific subtypes were correlated with poorer mental health outcomes. However, our analyses did not reveal consistent patterns that would allow for a definitive determination of how individual IPV subtypes differently affect mental health outcomes. Nevertheless, we observed that increasing severity of physical IPV tended to have a notable impact on post-traumatic stress disorder (PTSD). Conversely, increasing severity of psychological IPV was consistently associated with depression. While sexual IPV severity was explored in fewer studies, the evidence regarding its impact on various mental health outcomes was less conclusive. To achieve a comprehensive understanding of the mechanism by which IPV severity is related to mental health it may be time to take an alternative approach to measuring IPV severity. No IPV measures assessed the acceptability of the content to people who have experienced IPV. This is an important omission with significant consequences for the validity of the evidence base.